Far from home? A new locality record of Falcaustra sanjuanensis (Nematoda: Kathlaniidae) in a new host from the Brazilian Amazon - Oliveira da Silva, Leandro Mauricio (2024)
Studies on the helminth parasites of South American freshwater turtles are rare and punctual. The parasitic fauna of Kinosternon scorpioides’ nematodes from Brazil is restricted to only four species: Serpinema magathi, Serpinema monospiculatus, Serpinema pelliculatus and Spiroxys figueiredoi. The present work aimed to report the occurrence of the species Falcaustra sanjuanensis (Nematoda: Kathlaniidae), a parasite of an anuran from Argentina, in the large intestine of K. scorpioides from the Brazilian Amazon. The specimens of freshwater turtles were collected, anesthetized, and euthanized; the nematodes found were fixed in 90 °GL ethanol and analyzed by light microscopy and scanning electron microscopy. The nematodes showed some morphological and morphometric variations when compared with the original description of the species. Here we present new locality and host records for F. sanjuanensis and a new parasite record for K. scorpioides from Brazil.